Food Bank Use Prior to Homelessness - Ali Jadidzadeh; Ronald Kneebone (The School of Public Policy Publications)
This policy brief investigates the relationship between food bank usage and homelessness, examining how individuals and families respond to financial shocks that threaten their ability to maintain a home.